'Foresting' the grassland: Historical management legacies in forest-grassland mosaics in southern India, and lessons for the conservation of tropical grassy biomes. (August 2018) - Joshi, Atul Arvind; Sankaran, Mahesh; Ratnam, Jayashree
Abstract: Colonial encounters with tropical ecosystems were primarily driven by profit-oriented management practices; witness the extensive network of timber and forestry practices that were set up across colonial India. In contrast, the colonial engagement with the montane forest-grassland mosaics of the higher reaches of the Western Ghats in southern India was marked by intensive investment in vegetation management by colonial foresters that yielded no profits. In this archival study, we trace the history of extensive vegetation transformation in this landscape from the early nineteenth to the early twentieth century. We show how the misperception that the grasslands within this mosaic must have resulted from tree felling, fire-setting and buffalo grazing by indigenous communities led colonial foresters into a century-long effort at 'foresting' the grasslands, primarily through large-scale planting of exotic tree species. These efforts persisted despite economic losses and ecological evidence that native tree seedlings planted in the grasslands repeatedly failed to establish. These policies continued unabated into the late twentieth century in newly independent India. Today, the once picturesque landscapes of these ancient forest-grassland mosaics are diminished by large-scale plantations of exotic species. Some of these species have become invasive and pose significant threats to the remnant natural grasslands. While this historical narrative is set in the forest-grassland mosaics of southern India, it finds striking parallels in the current day, with grasslands and savannas globally threatened by the misperception that they are 'degraded ecosystems' that can be 'forested' or converted to other 'productive' land uses. We suggest that this case history portends the potential fates of many of earth's threatened tropical grasslands and savannas. Highlights: Colonial foresters misperceived Indian tropical grasslands as degraded ecosystems. This led to natural tropical grassland transformation into exotic tree plantations. Exotic trees became invasive in grasslands, causing biodiversity and habitat loss. Even today, tropical grasslands are misperceived, mismanaged, & threatened globally. Without recognition as legitimate ecosystems, these grasslands face a bleak future.